Synthesis and Characterization of Phenylphosphine Oxide Containing Perfluorocyclobutyl Aromatic Ether Polymers for Potential Space Applications - Jin, Jianyong; Smith, Dennis W; Topping, Chris M; Suresh, S; Chen, Shengrong; Foulger, Stephen H; Rice, Norman; Nebo, Jon; Mojazza, Bob H (Macromolecules, 2003)
A novel class of phenylphosphine oxide (PPO) containing perfluorocyclobutyl (PFCB) polymers has been developed for potential use as multifunctional materials in space environments. The reaction of p-BrArOCFCF2 (for Ar = phenyl and biphenyl) with tert-butyllithium affords the lithium reagent smoothly below −20 °C. Subsequent substitution with phenylphosphonic dichloride provides the first bis(trifluorovinyl ether) monomers containing the PPO group. Polymerization proceeds thermally above 150 °C to give polymers that exhibit glass transition temperatures of 169 and 224 °C, respectively, and catastrophic weight loss by TGA in N2 and air above 450 °C (10 °C/min). Copolymerization with bis(4,4‘-trifluorovinyloxy)biphenyl affords film-forming transparent thermoplastic copolymers with high T g (>140 °C) and good thermal stability (>450 °C). Initial evaluations with ground-based simulation of atomic oxygen (AO) rich space environments indicate that the PPO group imparts significant space durability to PFCB polymers.